2013
DOI: 10.7897/2230-8407.04740
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo Controlled Clinical Study to Evaluate the Effects of Garcinia Caplets in Obese Subjects

Abstract: Obesity and its concomitant health risks are among the most common conditions managed by health care practitioners. The limited long-term effectiveness of conventional weight management has led to researching alternative medicine and one which is widely accepted is the herbal products by virtue of its safety in long term use. The study was conducted to evaluate effect of caplet of Garcinia extract with reference to reduction in BMI and skin fold thickness in obese individuals. This study was performed accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One study was excluded from the meta‐analysis because of incomplete data. This study reported a significantly greater reduction in BMI in those taking G. cambogia compared to placebo . Combination preparations containing G. cambogia also had a non‐significant effect, with SMD –0.44 (95% CI –1.03, +0.15; P = 0.14) compared to placebo in 399 participants.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…One study was excluded from the meta‐analysis because of incomplete data. This study reported a significantly greater reduction in BMI in those taking G. cambogia compared to placebo . Combination preparations containing G. cambogia also had a non‐significant effect, with SMD –0.44 (95% CI –1.03, +0.15; P = 0.14) compared to placebo in 399 participants.…”
Section: Resultsmentioning
confidence: 67%
“…Of the five studies reporting on adverse events, all reported no significant differences in adverse events between the intervention and placebo groups . Of the seven studies reporting on treatment‐related adverse effects, five reported no effects, one reported no difference between the intervention and placebo groups, and one reported increased unpleasant gastrointestinal effects of the intervention compared to placebo (affecting 8 vs 0 participants)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation